Legal protection against licence plate businesses that produce licence plates for stolen vehicles - Dewa Satrya Utama; HR Adianto Mardijono (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
Vehicle license plate numbers include a unique identity that distinguishes one vehicle from another. Many modify vehicle license plates because of their ordinary shape, because of the large number of enthusiasts in modifying vehicle license plates, the roadside vehicle license plate service business is open, the negative side is to create new ideas for vehicle theft criminals to make fake plates at roadside vehicle license plate service entrepreneurs to replace the original license plates from the car they are stealing, But the owner of the vehicle license plate did not know that it was the result of theft. The actions of the perpetrators of making vehicle license plates on the roadside are categorized as criminal acts in articles 55 and 56 of the Criminal Code are considered to have participated in running. Therefore, legal protection is needed for vehicle license plate service entrepreneurs who make vehicle license plates do not know that the vehicle is the result of theft. The purpose of this study is to find out how legal protection for vehicle license plate service entrepreneurs accused of being plotters of vehicle theft, this study uses normative methods.